2002
DOI: 10.1046/j.1523-1755.2002.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGF-β and fibrogenic genes in transplant recipients with tacrolimus and cyclosporine nephrotoxicity

Abstract: This study compares the intrarenal expression of TGF-beta and profibrogenic genes in renal transplant recipients treated with Tac and CsA. The results show that patients diagnosed with Tac nephrotoxicity exhibit increased expression of profibrogenic genes compared to CsA nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 32 publications
6
88
0
2
Order By: Relevance
“…Although the present results are directed at an understanding of cyclosporine nephrotoxicity, our previous studies 15,[25][26][27][28][29] also demonstrate that TGF-␤ participates in both the immunosuppressive and nephrotoxic effects of tacrolimus and sirolimus. It is not known whether adjunctive therapy with a TGF-␤-neutralizing agent would also reduce the nephrotoxic effects of these 2 immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present results are directed at an understanding of cyclosporine nephrotoxicity, our previous studies 15,[25][26][27][28][29] also demonstrate that TGF-␤ participates in both the immunosuppressive and nephrotoxic effects of tacrolimus and sirolimus. It is not known whether adjunctive therapy with a TGF-␤-neutralizing agent would also reduce the nephrotoxic effects of these 2 immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by in vitro, in vivo, and clinical studies, we have demonstrated induction of TGF-␤ with other immunosuppressive agents such as tacrolimus and sirolimus. [25][26][27][28][29] Therefore, it is attractive to hypothesize that anti-TGF-␤ antibody may provide similar benefits to counteract adverse nephrotoxic effects observed with long-term use of these drugs as well.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is the profibrotic property of calcineurin inhibitors (CNIs). Cyclosporin and especially tacrolimus have been shown to upregulate transforming growth factor β in transplanted patients (38). Transforming growth factor β is thought to be of major importance in the development of peritoneal fibrosis (39).…”
Section: Discussionmentioning
confidence: 99%
“…Implicated fibrogenic cytokines include TGF-␤, matrix metalloproteinase-9, and PDGF. [41][42][43] Other investigators have focused on the pathogenic role of dysregulation of the RAAS. For example, CsA has been shown to increase transcription of angiotensin II receptors.…”
Section: Chronic Nephrotoxicitymentioning
confidence: 99%